Education on maintaining ear and hearing health for medical students at Universitas Muhammadiyah Yogyakarta - Daniswara, Deoni; Widuri, Asti; Fakhriani, Rizka; Abdullah, Adnan (Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada, 2024)
Introduction: Maintaining ear health and hygiene is crucial as it directly influences one's auditory capabilities and overall quality of life. Previous research on university students states that almost all respondents (98%) do their ear cleaning routinely, which causes ear pain, ringing, and itching. According to WHO data, over 1 billion young individuals are susceptible to hearing loss due to exposure to noise or loud sounds. Therefore, the dedicated team provided education to students in the Medical Study Programme, Faculty of Medicine and Health Sciences, Universitas Muhammadiyah Yogyakarta, on maintaining ear and hearing health to avoid hearing impairment.Methods: The participants of this community service consisted of 27 students. This community service program was carried out in January 2024. The methods used in implementing this program in detail included preparing a pretest, providing educational material on how to maintain ear and hearing health, and ending with posttest activities.Results: On average, Participants who participated in this community service activity were 18-20 years old. Of the participants, only 21 participated in the pretest session, and only 24 participated in the posttest session. The results of the analysis showed that there was a significant increase in knowledge (p=0.001) between before education and after education.Conclusions: In this study, medical students' knowledge level at Universitas Muhammadiyah Yogyakarta regarding how to maintain ear and hearing health still needs to be improved. Education on maintaining ear and hearing health proved significant in improving knowledge.